Opioid free treatment algorithm for ED headache management: Effect on revisit rate - Miller, Justin; Koons, Laura; Longyhore, Daniel (The American journal of emergency medicine, 2020)
The opioid epidemic is a crisis leading to over utilization of resources within emergency departments (EDs). We assessed how implementation of an opioid-free headache and migraine treatment algorithm in the ED impacted patient centered outcomes. This was a retrospective review of patients presenting to EDs across a health network with a primary diagnosis of headache or migraine. Two analyses were completed comparing patients presenting before and after implementation of an opioid-free treatment algorithm and patients treated with or without opioids in the ED. The primary outcome was incidence of an ED revisit within thirty days. Secondary outcomes included ED length of stay, admission rate, and incidence of revisit during the entire study period. In total, 2953 patient encounters were included. Incidence of revisit within thirty days was lower in the post- (84/1339, 6.3%) versus pre-algorithm group (133/1614, 8.2%; odds ratio [OR] 0.75, 95% confidence interval [CI] 0.56–0.99; p = 0.049), as was the incidence of revisit within the entire study period (9.2% vs. 12.1%; OR 0.74, CI 0.58–0.93; p = 0.014). In the secondary analysis, patients treated with opioids had a higher incidence of revisit within thirty days (51/335, 15.2%) compared to those not treated with opioids (166/2618, 6.3%). The opioid group also had a higher incidence of admission rates and median ED length of stay. Opioid use in the ED to treat patients with headaches or migraines may have several negative ramifications including increased risk of revisit, hospital admission, and increased ED length of stay.